What are the affordances of information and communication technologies? - Grainne Conole; Martin Dyke (Association for Learning Technology, 2004)
The paper examines the notion that Information and Communication Technologies (ICT) have affordances that epitomize the features of our late modern age (Giddens, 1991) and explores whether these affordances (Salomon, 1993, p. 51) can be used to facilitate particular approaches to educational practice. It argues that a clear articulation of these affordances would enable us to understand how these technologies can be most effectively used to support learning and teaching. We believe that any one affordance can be considered to have both positive and negative connotations and the paper draws on social and educational theory to provide an initial taxonomy of these affordances.